1982
DOI: 10.1149/1.2124119
|View full text |Cite
|
Sign up to set email alerts
|

Polysilicon / SiO2 Interface Microtexture and Dielectric Breakdown

Abstract: An analysis has been made of interfacial texture created during the wet oxidation of polycrystalline silicon (polysilicon) over the temperature range 950°–1100°C, and the effect of this texture on oxide breakdown. Four types of interfacial textural features are described: interface roughness due to initial polysilicon surface texture, “bumps” caused by anomalous polysilicon nucleation at local sites of contamination, “protuberances” that occur during oxidation, and inclusions of unoxidized silicon within the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

1985
1985
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(14 citation statements)
references
References 2 publications
0
14
0
Order By: Relevance
“…Recent efforts have attempted to enhance current injection at the insulator/silicon interface for EEPROM-type memory cell applications, leading to the study of polysilicon oxides (polyoxides) [1]- [5]. An alternate application of "on-chip" capacitors with a dual-polysilicon process has also prompted the characterization of thin oxides grown over polysilicon [6], [7].…”
mentioning
confidence: 99%
“…Recent efforts have attempted to enhance current injection at the insulator/silicon interface for EEPROM-type memory cell applications, leading to the study of polysilicon oxides (polyoxides) [1]- [5]. An alternate application of "on-chip" capacitors with a dual-polysilicon process has also prompted the characterization of thin oxides grown over polysilicon [6], [7].…”
mentioning
confidence: 99%
“…Here, the O interstitial diffusion acted as a knife, cutting the Si core into nano-fragments, and diffused O formed SiO x with the rest of the neighboring Si parts. The volume ratios of the nano-Si:SiO x actually relied on the diffusion conditions such as the amount of O participated in the thermal diffusion [ 17 ]. Table 2 lists the weight percentages of Si and O in nano-Si/SiO x particles examined by X-ray fluorescence (XRF), which confirms the oxygen content of produced SiO x increases as long as the thermal oxidation time increase.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the observed increase in roughness for increasing polyoxide thickness is predominantly caused by differential oxidation of grains with varying surface orientations as well as preferential oxidation along grain boundaries (13,14). Previous studies using cross-sectional TEM have shown that, as thermal oxidation proceeds, the oxidation front becomes more irregular and leads to oxide thickness nonuniformities and cusp-like structures pointing into the oxide, which are favorable geometries for local field enhancement (12,20,21). The data plotted in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Up until now, only the effects of interface roughness on field enhancement have been considered. However, for relatively thick thermal P01yoxides (> 100 nm), a number of studies have shown that, due to nonuniform oxidation rate, large protuberances and inclusions can result (12,20,21). This leads to SiO~ thickness nonuniformities in the vicinity of the protuberances with a resulting structure in which the upper and lower oxide/polysilicon interfaces are nonconformal.…”
Section: Resultsmentioning
confidence: 99%